61. The World-Wide Inaccessible Web, Part 2: Internet routes - Baggaley, Jon; Batpurev, Batchuluun; Klaas, Jim (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
In the previous report in this series, Web browser loading times were measured in 12 Asian countries, and were found to be up to four times slower than commonly prescribed as acceptable. Failure of webpages to load at all was frequent. The current follow-up study compares these loading times with the complexity of the Internet routes linking the Web users and the Web servers hosting them. The study was conducted in the same 12 Asian countries, with the assistance of members of the International Development Research Centre’s PANdora distance education research network. The data were generated by network members in Bhutan, Cambodia, India, Indonesia, Laos, Mongolia, the Philippines, Sri Lanka, Pakistan, Singapore, Thailand, and Vietnam. Additional data for the follow-up study were collected in China. Using a ‘traceroute’ routine, the study indicates that webpage loading time is linked to the complexity of the Internet routes between Web users and the host server. It is indicated that distance educators can apply such information in the design of improved online delivery and mirror sites, notably in areas of the developing world which currently lack an effective infrastructure for online education.